Rise of netholicism: A comprehensive review of internet addiction among today’s youth - Yogesh Kumar; Om P. Dhakar (Journal of Education and Health Promotion)
The rise of internet addiction among today’s youth, termed “netholicism,” has become a pressing concern in the digital era. The pervasive nature of internet usage among youth, driven by factors such as individual vulnerabilities, societal norms, and addictive online activities, contributes to the development of problematic internet use. Excessive internet use has profound psychological effects, including depression, anxiety, and social isolation, while also leading to physical consequences such as sedentary lifestyles and sleep disturbances. This comprehensive review explores the multifaceted aspects of internet addiction, from its psychological and physical impacts to its social and spiritual ramifications. This article uses a literature review methodology to analyze research on the pervasive nature of internet usage, termed “netholicism,” among youth. It synthesizes and evaluates prior findings to understand the factors contributing to netholicism and young individuals’ involvement in internet usage following the ramifications of netholicism are reflective psychological, physical, sociological, and spiritual effects in every domain on youth. The study analyzed 50 articles from reputable online databases, focusing on internet usage. Out of the 50 articles, 16 were cited, meeting inclusion criteria, including publication within 2019–2024, rigorous peerreview, and reputable database indexing. As per the findings of the research, it has been observed that netholicism (or internet addiction) represents a complex and multifaceted phenomenon with the underlying factors contributing to internet addiction and its psychological, physical, social, and spiritual impacts. Socially, internet addiction hinders real-life connections and emotional intelligence, while ethically and spiritually, it raises concerns about identity and moral relativism in the digital realm. Interventions and treatment approaches encompass psychoeducation, therapy, and digital literacy promotion. Looking ahead, the proliferation of internet addiction poses challenges exacerbated by technological advancements, requiring collaborative efforts to mitigate its adverse effects and promote a healthier relationship with technology among future generations.